Park Square Building at 31 Saint James Avenue, ca. 1930 - Unknown (Tufts Archival Research Center, 2005)
Elevated view northeast of the Park Square Building at 31 Saint James Avenue, located between Arlington Street to the east and Berkeley Street to the west. The facade of the building faces south-southeast. Several automobiles, large signs and a wooden structure are located in a parking lot located across Saint James Avenue from the Park Square Building. Other automobiles line Saint James Avenue and Berkeley Street, which is visible near the lower-left side of the photograph. Several pedestrians are included in the photograph. 7 1/2 x 9 1/2, 7 1/2 x 9 7/8 overall Photographs